1940
DOI: 10.1002/j.1537-2197.1940.tb14209.x
|View full text |Cite
|
Sign up to set email alerts
|

Studies on the Nutrition of Fungi. Iv. Factors Influencing the Growth of Some Thiamin‐requiring Fungi

Abstract: bined and dried at 100°C. to constant weight. Thus each figure given in the following tables, unless otherwise stated, represents the composite weight of five cultures. The actual weight of mycelium obtained under controlled conditions has been made the criterion for the evaluation of the comparative effectiveness of various factors. However, it should be emphasized that biological phenomena cannot be reduced to mathematical figures without making a generous allowance for the frequent and often disconcerting f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

1940
1940
1962
1962

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 53 publications
(16 citation statements)
references
References 4 publications
1
15
0
Order By: Relevance
“…Among the amino acids tested glycine, alanine, arginine and glutamic acid supported good growth of the present fungus. These acids have generally been reported to be good sources of nitrogen for Mucorales by a number of authors (LOCKWOOD 1936, LEONIAN andLILLY 1940;LILLY 1956, RAIZADA 1957). The only amino acid whidi failed to induce satisfactory growth was histidine.…”
Section: Discussionmentioning
confidence: 98%
“…Among the amino acids tested glycine, alanine, arginine and glutamic acid supported good growth of the present fungus. These acids have generally been reported to be good sources of nitrogen for Mucorales by a number of authors (LOCKWOOD 1936, LEONIAN andLILLY 1940;LILLY 1956, RAIZADA 1957). The only amino acid whidi failed to induce satisfactory growth was histidine.…”
Section: Discussionmentioning
confidence: 98%
“…The stimulation of growth of Phycomyces blakesleeanus by the addition of organic acids to the medium had already been described by several groups of workers (e.g. Leonian & Lilly, 1940), while the Wisconsin workers mentioned above had already described their use for submerged cultures of Penicillium. Marloth (1931) had also shown that the addition of citrate to media containing sucrose increased the growth of two species of Penicillium.…”
Section: T Calam and D J D Hockenhullmentioning
confidence: 90%
“…On the other hand the amide had only a slight, positive efteet, eqnal to that of fnmarie acid after 35 days. The stimulative elfect of tartarie acid on fungal growth (Leonian and Lilly 1940), may he dne to its relatively close connection with the acids of the Krehs cycle. Therefore, its pre.sence in the ba.sal medium may possibly diminish the positive effect of the compounds added.…”
Section: Experiments and Kesultsmentioning
confidence: 99%
“…It was suggested, that the beneficial effect of these two dicarboxylic amino acids is bound up with their effect on the initial stages of growtb, at which stage ibey would he superior to every other amino acid, providing they have no toxic-effect on the organism and that there exists no complete helerolrophy which could prevent the synthesis of any particular amitio acid.However, since several organisms are ahle readily to form ghttamic acid hy reductive aniination of a-ketoglntaric acid, the stimulative effect of the dicarboxylic amino acids should not, perhaps, he ascribed to the amino acids as such hut to their carbon skeleton. As estahlished by Leonian and Lilly (1940), organic acids have a stimulative effect on fungal growth, and it seems not nnreasonahic l<( suppose that in the preseut case a-ketoglutaric, oxaloacetic, and probably other acids involved in the Krebs tricarhoxylic acid cycle could he effective as substittttes. Thus, the present study was undertaken in order to compare the growth effects of the two amino acids concerned, as well as of their corresponding keto-acids and fumaric acid.[584]…”
mentioning
confidence: 99%